The Connections among Problematic Usage of the Internet, Psychological Distress, and Eating Disorder Symptoms: A Longitudinal Network Analysis in Chinese Adolescents. - Lin, Yang; Ren, Yaoxiang; Barnhart, Wesley R.; Cui, Tianxiang; Zhang, Jihong; He, Jinbo (International Journal of Mental Health & Addiction, 2025)
With a longitudinal design, the current research examined the relationships among problematic usage of the internet (PUI), psychological distress (PD), and eating disorder (ED) symptoms in a sample of Chinese adolescents. Data were from a project with three waves of data collection (N = 589; aged 14 ~ 18 years at baseline) at 6-month intervals. A set of questionnaires were used to assess PUI, PD, and ED symptoms at each wave of data collection. A longitudinal network analysis was conducted. Self-induced vomiting or laxative use as an ED symptom at Time t-1 positively predicted all PUI subscales (i.e., mental withdrawal, neglect, control disorder) at Time t, while desire to lose weight as another ED symptom positively predicted all other ED symptoms. Moreover, PD might play an important role in bridging ED symptoms and PUI due to its associations with both PUI (i.e., mental withdrawal) and ED symptoms (i.e., fear of weight gain, desire to lose weight, self-induced vomiting or laxative use, and loss of control eating). The current study extended network theory to better understand the co-existence of PUI, PD, and ED symptoms in Chinese adolescents. Intervention targeting PUI, PD, desire to lose weight, and self-induced vomiting or laxative use may be effective in reducing the co-existence of PUI and ED symptoms.